Mathématiques
Ayewinho
26

Aider moi svp A= 1+ ( 2x+7)= B= 6 - ( 2 + 4x)= C = ( -2x + 8)= D= 4x ( 6x + 4 ) + 2 ( 5x + 3)= E= 6 x ( 2x + 5) -4 ( 2x + 8)= F= 3x - 8 - 2 ( 3x + 1 )= G = ( 3x - 4 ) - ( - 8x + 4 )= H= ( 6x2 - 3x + 5) + ) - ( -4x2 - 3x - 4 )= I = 4 ( 6x - 4 ) - 3 (x - 9 )=

+2
(2) Réponses
caroline974181

A= 1+ ( 2x+7) A = 1 + 2x + 7 A = 2x + 8 B= 6 - ( 2 + 4x) B = 6 - 2 - 4x B = - 4x + 4 C = ( -2x + 8) C = - 2x + 8 D= 4x ( 6x + 4 ) + 2 ( 5x + 3) D =  24x² + 16x + 10x + 6 D = 24x² + 26x + 6 E= 6 x ( 2x + 5) -4 ( 2x + 8) E = 12x² + 30x - 8x - 32 E = 12x² + 22x - 32 F= 3x - 8 - 2 ( 3x + 1 ) F = 3x - 8 - 6x - 2 F = - 3x - 10 G = ( 3x - 4 ) - ( - 8x + 4 ) G = 3x - 4 + 8x - 4 G = 12x - 8 H = ( 6x2 - 3x + 5) + ) - ( -4x2 - 3x - 4 ) H = 6x² - 3x + 5 + 4x² + 3x + 4 H = 10x² + 9   I = 4 ( 6x - 4 ) - 3 (x - 9 ) I = 24x - 16 - 3x + 9 I = 21x - 7

clementchamoul

A= 1 + ( 2x+7) A = 1 + 2x + 7 A = 2x + 8 B= 6 -( 2 + 4x) B = 6 -2 - 4x B = -4x + 4 C = ( -2x + 8) C = -2x + 8 D= 4x ( 6x + 4 ) + 2 ( 5x + 3) D =  24x² + 16x + 10x + 6 D = 24x² + 26x + 6 E= 6 x ( 2x + 5) -4( 2x + 8) E = 12x² + 30x - 8x -32 E = 12x² + 22x -32 F= 3x -8 -2 ( 3x + 1 ) F = 3x -8 -6x -2 F = - 3x -10 G = ( 3x - 4 ) - ( - 8x + 4 ) G = 3x -4 + 8x -4 G = 12x -8 H = ( 6x2 - 3x + 5) + ) - ( -4x2 - 3x - 4 ) H = 6x² - 3x + 5 + 4x² + 3x + 4 H = 10x² + 9   I = 4 ( 6x - 4 ) - 3 (x - 9 ) I = 24x -16 -3x + 9 I = 21x -7

Ajouter une réponse